2008
DOI: 10.1093/humrep/den017
|View full text |Cite
|
Sign up to set email alerts
|

High and low BMI increase the risk of miscarriage after IVF/ICSI and FET

Abstract: Obese and underweight women have an increased risk of miscarriage, and hormonally substituted FET is associated with an even higher MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
117
5
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(134 citation statements)
references
References 72 publications
11
117
5
1
Order By: Relevance
“…In a Finnish Table 2. Comparison of mean body composition in primigravidas and multigravidas who miscarried with those who did not study, the miscarriage rate was found to be higher at the extremes of weight compared with normal-weight women [12] . In a study examining the probability of pregnancy after assisted reproduction the odds ratio was 0.73 for class 1 obese women and 0.5 for class 2-3 obese women, compared with women in the normal BMI category [13] .…”
Section: Discussionmentioning
confidence: 85%
“…In a Finnish Table 2. Comparison of mean body composition in primigravidas and multigravidas who miscarried with those who did not study, the miscarriage rate was found to be higher at the extremes of weight compared with normal-weight women [12] . In a study examining the probability of pregnancy after assisted reproduction the odds ratio was 0.73 for class 1 obese women and 0.5 for class 2-3 obese women, compared with women in the normal BMI category [13] .…”
Section: Discussionmentioning
confidence: 85%
“…One was the study of Veleva et al (2008) , which showed that the BMI graph curve that represents how BMI affects the miscarriage rate is U-shaped, meaning that patients of low weight also has their increased risk, independent of patient age ( Figure 3 ). Moreover, the revision of Rittenberg et al, 2011 revealed increased miscarriage rate in 14 studies (RR 1.36, 95 % CI 1.13 to 1.64, p et al, 2010, despite the rate being increased, this increase was not significant, as in Vilarino et al, 2011, Zhang et al, 2010and Sathya et al .,2010.…”
Section: Miscarriage Ratementioning
confidence: 99%
“…However, not all studies corroborate these findings (6,11). The impact of obesity on miscarriage rates in ART is more controversial (5,9,(12)(13)(14)(15).…”
mentioning
confidence: 99%